A COMPARATIVE STUDY OF STUDENTS’ SPEAKING SKILL BASED ON EXTERNAL ENGLISH COURSE AND NON EXTERNAL ENGLISH COURSE AT ELEVENTH CLASS OF TOURISM SMK N 2 JAMBI - Longga Dwi Trisna; Wennyta Wennyta (JELT: Journal of English Language Teaching, 2019)
This research use quantitative research. This research use purposive sampling to take sample. This research uses one class to interview and test. This research took XII Tourism as a sample, XII Tourism consist of 33 students. After interview and test the result of the research there is students who take an external English course and students who don’t. From all 33 students 15 of them take an external English course and 18 do not take an external English course. In percent form, approximately 45, 45% of students take an external English course and approximately 54, 54% of students don’t. The result of test and interview is the students speaking ability does not completely relate to weather they take an external English course or not. Because when it comes to language, we have to use it to master it. The students have to use it even when they not in class so they will used to using it. The other factor that determined students ability, and there is circle and habits.  It can be conclude that H0 is accepted and Ha is rejected. It is suggested to the future researchers who are interested in deeper studying about how to make the students more excited to learn English especially speaking. The future researchers can use this research as a reference.